Pengawasan Kementerian Kesehatan Dan BPOM Atas Peredaran Obat Sirup Anak Yang Menyebabkan Gagal Ginjal Akut (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2023)
At the end of August 2022 there was an event that really agitated the Indonesian people, especially for parents, where cases of death in children were caused by syrup drugs consumed by children containing chemicals that can cause GGAPA in children which can lead to death. The Health Service Unit of the Ministry of Health received a report noting that as of February 5, 2023 the number of cases was 326 children affected by GGAPA spread across 27 provinces in Indonesia. Kemenkes quickly issued an instruction due to an increase in cases of AKI aged 0-5 years in various regions of Indonesia, which was aimed at all pharmacies not being allowed to sell syrup for children for a while. As stated in (SE) Number SR.01.05/III/3461/2022 concerning Obligations for Epidemiological Investigation and Reporting of Atypical Progressive GGAPA, the instruction was issued on 18 October 2022. BPOM revealed multiple entities here due of suspicions of irresponsible supervision leading to the distribution of pharmaceuticals containing harmful chemicals, which led to severe kidney failure in infants, notably those between the ages of 1 and 5. The authors got interested in investigating the legal responsibility of the Ministry of Health and BPOM for the distribution of syrup medications that induce acute renal failure in children and ultimately lead to death as a response to these issues. The authors conducted their investigation utilizing normative legal research methods in the hopes of more easily resolving these legal issues. Findings from the investigation indicate that BPOM, as a state agency and legal subject, must assume responsibility for any failures it may have had in preventing the distribution of medications known to cause death in children. Keywords: acute kidney failure in children; dangerous drugs; liability Abstrak Sebuah insiden yang terjadi menjelang akhir Agustus 2022 secara signifikan menginspirasi masyarakat Indonesia, terutama para orang tua. Kematian pada anak-anak dikaitkan dengan penggunaan obat sirup, yang mengandung zat yang bisa menyebabkan GGAPA, yang bisa mengakibatkan kematian. GGAPA menimpa 326 anak pada periode 5 Februari 2023 di 27 provinsi di Indonesia, menurut laporan yang disampaikan kepada Unit Pelayanan Kesehatan Kementerian, karena meningkatnya kasus GGAPA usia 0-5 tahun di seluruh Indonesia, Kemenkes dengan cepat mengeluarkan instruksi kepada seluruh apoteker untuk menghentikan sementara penjualan sirup anak. Arahan tersebut diterbitkan pada tanggal 18 Oktober 2022 dan tertuang pada SE No.SR.01.05/III/3461/2022. BPOM mengungkapkan banyak entitas karena kecurigaan pengawasan yang tidak bertanggung jawab yang mengarah pada distribusi obat-obatan yang mengandung bahan kimia berbahaya, yang menyebabkan gagal ginjal yang parah pada bayi, terutama yang berusia antara 1 dan 5 tahun. Penulis tertarik untuk menyelidiki tanggung jawab hukum dari Kemenkes dan BPOM untuk pendistribusian obat sirup yang mengakibatkan GGAPA dan akhirnya berujung pada kematian sebagai respon atas permasalahan tersebut. Penulis menggunakan metode penelitian hukum normatif dengan harapan bisa lebih mudah menyelesaikan permasalahan hukum tersebut. Hasil investigasi menunjukkan bahwasanya BPOM, sebagai lembaga negara dan subjek hukum, harus bertanggung jawab atas kegagalan yang mungkin terjadi dalam mencegah peredaran obat yang diketahui menyebabkan kematian pada anak. Kata kunci: gagal ginjal akut pada anak; obat berbahaya; pertanggungjawaban